2012
DOI: 10.1111/j.1464-410x.2012.11219.x
|View full text |Cite
|
Sign up to set email alerts
|

Ureteric stent placement with extraction string: no strings attached?

Abstract: E 1 0 6 9What ' s known on the subject? and What does the study add? Of patients treated with an indwelling ureteric stent 80 -90% experience lower urinary tract symptoms that are a hindrance to health-related quality of life. The prevalence of the extraction/retrieval string after ureteroscopy for stone disease and stent placement varies signifi cantly between surgeons and published series, but the benefi ts of eliminating the need for a secondary procedure such as cystoscopy and stent removal, as well as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 9 publications
1
44
1
Order By: Relevance
“…Although studies have previously called into question the necessity of ureteral stenting after uncomplicated lithotripsy, 8,12 postoperative stent placement remains common and the question of whether to stent remains unresolved. 13 The results of this survey identify the morbidity that can be associated with stent removal and provides insight into the experiences and preferences of urologic patients who undergo these procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although studies have previously called into question the necessity of ureteral stenting after uncomplicated lithotripsy, 8,12 postoperative stent placement remains common and the question of whether to stent remains unresolved. 13 The results of this survey identify the morbidity that can be associated with stent removal and provides insight into the experiences and preferences of urologic patients who undergo these procedures.…”
Section: Discussionmentioning
confidence: 99%
“…We recognize that the choice of a specific method can be influenced by multiple factors, including cost, resources, and the risk of accidental dislodgement when a string is left in place. 12 Delayed pain after stent removal appears to be underappreciated by physicians. As a result, patients often report that they were not adequately counseled about this potential morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…A computerbased system that tracks ureteral stents and automatically sends a reminder to both the patient and the urologist's phones has been described [24]. BStents on strings^have been proposed where one end of the stent is tied to a string which is externalized for easy removal later [25]. Treatment of all cases with a DJ stent should be considered incomplete unless the stent is removed.…”
Section: Resultsmentioning
confidence: 99%
“… report on the results of a prospective randomised trial analysing stented patients with or without the extraction strings attached, for both quality of life and postoperative complications after ureteroscopy for stone disease. This follows on from a retrospective series previously reported by the same group . It is pleasing to see the authors, who originally concluded that randomised trials are needed in this area, actually get on and do the trial!…”
mentioning
confidence: 92%